Mobile Prefetching and Web Prefetching: A Systematic Literature Review - Buyuktanir, Tolga; Aktas, Mehmet S. (SPRINGER INTERNATIONAL PUBLISHING AG, 2022)
Today, we see that prefetching systems are widely used to decrease the network traffic, data access latency, energy consumption, and computing performance inefficiency of data-intensive operations. However, prefetching is a concept used in different computing and IT fields such as microprocessor design, micro-controller design, hard disk design, database, network, web application, mobile application, etc. The fact that the concept of prefetching is used in different fields causes difficulties in literature review and research. Therefore, these studies need to be organized systematically for each field. This study presents a systematic literature review of prefetching related mobile and web applications to identify research gaps, define new study subject opportunities, and present future directions. We think that this study will make it easier for other researchers to work in this field with the research gaps and opportunities indicated.
Keywords: Web prefetching; Mobile prefetching; Systematic literature review; Intelligent techniques; Prefetching strategies; Computer Science